2010
DOI: 10.1111/j.1365-2893.2010.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal transmission of HIV despite persistently high transmission of hepatitis C virus in a Swedish needle exchange program

Abstract: The aim of this study was to examine the prevalence and incidence of HIV and hepatitis B and C (HBV and HCV) among injecting drug users in a Swedish needle exchange programme (NEP) and to identify risk factors for blood-borne transmission. A series of serum samples from NEP participants enrolled from 1997 to 2005 were tested for markers of HIV, HBV and HCV (including retrospective testing for HCV RNA in the last anti-HCV-negative sample from each anti-HCV seroconverter). Prevalence and incidence were correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
4
16
0
2
Order By: Relevance
“…While blood-borne viral hepatitis is common in the present study, less than 1% of the whole cohort reported to be HIV positive (Hakansson et al, 2008). This low prevalence of HIV is in accordance with HIV being less prevalent in injection drug users in the Swedish setting, compared to many other countries (Blomé et al, 2011), and results on causes of deaths should be seen in that perspective.…”
Section: Discussionsupporting
confidence: 87%
“…While blood-borne viral hepatitis is common in the present study, less than 1% of the whole cohort reported to be HIV positive (Hakansson et al, 2008). This low prevalence of HIV is in accordance with HIV being less prevalent in injection drug users in the Swedish setting, compared to many other countries (Blomé et al, 2011), and results on causes of deaths should be seen in that perspective.…”
Section: Discussionsupporting
confidence: 87%
“…Even for subjects with access to a NEP, continuing injection drug use poses repeated risks of exposure to HCV, as both the previously observed incidence data from the Malmö NEP and other reports indicate [25], [32], [33]. Another recent longitudinal study among young PWID with ongoing risk behaviour found that several subjects with signs of spontaneous viral clearance had subsequent detectable viremia with the original viral strain (suggesting recurrence rather than reinfection) [34].…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, we reported the incidence of HIV, HBV and HCV among new participants, registered in the NEP from 1997 throughout 2005 [25]. In summary, HIV prevalence and incidence was low (baseline prevalence 0.12% and incidence 0.08/100 person years at risk [pyr] among 831 subjects), whereas previous exposure to HBV was found among 28% (linked with a HBV incidence of 3.4/100 pyr).…”
Section: Methodsmentioning
confidence: 99%
“…More than 4,500 persons have enrolled since the start, and around 75% of participants are male. Prerequisites for enrolment in the NEP are self-reported injection drug use, age ≥ 20 years, signs of recent venepuncture, and consent to HIV testing [7]. The injected drugs in Sweden are mainly amphetamine and heroin, and among the population at Malmö NEP amphetamine is traditionally the most common main drug, followed by heroin [24].…”
Section: Methodsmentioning
confidence: 99%
“…At the needle exchange program (NEP) in Malmö, 91% tested positive for HCV [1990][1991][1992][1993], and in the same study HCV infection kept spreading despite free access to clean injection tools. The prevalence 1997-2005 at the same NEP was 60% [7]. The HCV incidence at Malmö NEP has recently been decreasing; however, the prevalence is still high.…”
Section: Introductionmentioning
confidence: 99%